Moroccan EFL Teachers’ Beliefs about the Potential Contribution of Multilingualism to the L3 English Classroom: To What Extent Is Multilingualism an Asset to L3 English Learners? - Ait Hammou, Yassine; Trimasse, Naima; Elghazi, Mohamed (International Journal of Linguistics and Translation Studies, 2024)
The current study set out to investigate Moroccan English language teachers’ educational beliefs about the potential of multilingualism for the L3 English classroom. Utilizing a mixed-method approach of investigation, this study employs two instruments to collect data: questionnaires and semi-structured interviews. An online questionnaire was completed by 169 teacher informants who participated in this study, 20 of whom were selected for the semi-structured interviews. Data were analyzed quantitatively and qualitatively. Findings revealed that teacher participants generally exhibited partial/moderate awareness of the usefulness of multilingualism to the L3 English classroom as they held moderate positive educational beliefs about its potential for fostering their multilingual learners’ L3 English. Hence, this study suggests that Moroccan L3 English teachers be encouraged to take maximum advantage of their students’ multilingualism in a way that is beneficial to their L3 English learners. Teacher education has a significant role in positively shaping L3 English teachers’ educational beliefs in that respect.